Hydroxyapatite/sodium alginate coatings electrophoretically deposited on titanium substrates: microstructure and properties - Moskalewicz, Tomasz; Warcaba, Maciej; Cieniek, Łukasz; Sitarz, Maciej; Gajewska, Marta; Boccaccini, Aldo R. (Applied Surface Science, 2021)
The aim of the present work was to develop the electrophoretic deposition (EPD) of composite bioinspired hydroxyapatite/sodium alginate (HA/SA) coatings on titanium and coatings characterization. The EPD was performed from water-based suspensions with different content of HA. The influence of the EPD parameters on the coating homogeneity, morphology and properties are discussed. Depending on the HA content in suspension, it was possible to obtain dense coatings with different amounts and sizes of HA agglomerates, exhibiting different surface morphology. The state of preparation of the substrate surface and the HA content in suspension significantly affects the coating adhesion. All composite coatings had better adhesion to chemically treated titanium in comparison with the adhesion of pure SA coatings. Strong variations of coating microstructure were observed depending on the HA content and suspension pH due to a cross-linking process between HA and SA. All coatings, regardless of the HA content revealed hydrophilic character. HA/SA coatings exhibited about 10% higher values of surface free energy than the pure SA ones. This work confirmed that EPD is a useful technique to co-deposit HA nanoparticles and SA to fabricate a wide range of coatings with tailored microstructure and surface morphology with potential for biomedical applications.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Bioinspired coatings; Electrophoretic deposition; Hydroxyapatite; Sodium alginate; Titanium